2019
DOI: 10.1186/s12933-019-0807-3
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial fat tissue in patients with diabetes mellitus: a systematic review and meta-analysis

Abstract: Background: Epicardial fat tissue (EFT) is the visceral fat distributed along the coronary arteries between the pericardium and the myocardium. Increases in EFT are closely related to the occurrence of diabetes mellitus (DM) and cardiovascular disease. To further understand the link between EFT and DM, we conducted a meta-analysis of the relevant literature. Methods: We systematically searched electronic databases for studies on EFT performed in DM patients and published up to 30 September 2018. We included da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 65 publications
(74 reference statements)
4
74
0
5
Order By: Relevance
“…Moreover, Iacobellis et al, 44 reported that type 1 diabetes is associated with excess EF regardless of BMI, since EF thickness was significantly higher in diabetic individuals compared to non-diabetics (7.2 ± 2.1 mm vs 4.9 ± 2.5 mm; p < 0.01). Similar results were observed by Kim et al, 26 (p = 0.022) and Li et al, 45 With aging, calcium deposition and loss of elastic fibers in the middle layer of the arteries are observed, leading to a decrease in their distensibility. 46 In the aortic artery, this fact stimulates the development of hypertension, diastolic dysfunction and heart failure.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, Iacobellis et al, 44 reported that type 1 diabetes is associated with excess EF regardless of BMI, since EF thickness was significantly higher in diabetic individuals compared to non-diabetics (7.2 ± 2.1 mm vs 4.9 ± 2.5 mm; p < 0.01). Similar results were observed by Kim et al, 26 (p = 0.022) and Li et al, 45 With aging, calcium deposition and loss of elastic fibers in the middle layer of the arteries are observed, leading to a decrease in their distensibility. 46 In the aortic artery, this fact stimulates the development of hypertension, diastolic dysfunction and heart failure.…”
Section: Discussionsupporting
confidence: 87%
“…EAT has a range of functions, including lipogenic capacity [20]. A number of researchers have focused on the adverse effects of EAT and confirmed this parameter as a marker of diabetic risk [8]. A previous study also revealed that EAT thickness was significantly higher in women with a history of GDM than controls [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a promising echocardiographic parameter, epicardial adipose tissue (EAT), has emerged that could complement the use of BMI to assess risk for GDM. EAT is closely related to metabolic syndrome and diabetes [7,8], and is an independent predictor of visceral adiposity, as measured by echocardiography [9]. This study aimed to investigate the association between the EAT thickness and GDM, and assess the efficacy of EAT thickness as a potential predictor for GDM at 16 weeks + 0 days to 19 weeks + 6 days before the diagnosis of GDM.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, we observed that obesity, measured by BMI, was associated with EAT after adjustment for several CV risk factors. A recent meta-analysis indicated that the amount of EAT is significantly higher in patients with diabetes mellitus than in patients without diabetes mellitus [ 22 ]. Similarly, we observed a higher prevalence of diabetes mellitus in patients with high EAT volume compared with those with low EAT volume.…”
Section: Discussionmentioning
confidence: 99%